Implementation of Stock Opname Procedures for General Affair Warehouse Inventory at PT Bernofarm Pharmaceutical Company - Rahmadani Sandrigus Shanon; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research investigates the implementation of stock opname procedures in the General Affair warehouse at PT Bernofarm Pharmaceutical Company, a major pharmaceutical manufacturer. The study responds to the problem of discrepancies in inventory data, which can disrupt operations due to inaccurate recording or delays in documentation. The objective is to analyze the effectiveness and structure of stock opname procedures in controlling non-productive inventory. A qualitative descriptive method was employed, utilizing observation and interviews with Accounting and General Affair warehouse staff to collect primary data. The findings reveal that stock opname at PT Bernofarm is conducted periodically through coordinated stages: scheduling, preparation of inventory data, physical inspection, data reconciliation, reporting, and inventory adjustment. The procedures are carried out collaboratively between the Accounting and General Affair divisions, with clearly defined responsibilities and documentation such as stock cards, credit memos, and goods receipts. Despite a difference in theoretical and practical implementation—where inventory recording is managed by warehouse staff rather than accounting—the presence of functional segregation and supervisory checks ensures effective internal control. The study concludes that a structured and consistent stock opname process improves data accuracy, minimizes discrepancies, and enhances accountability. This research is limited to non-productive inventory in a single company division, and further studies are suggested to explore digital solutions or comparative analyses across industries.